Preparation and Characterization of novel metal complexes containing hydrazone derived from camphor and 2,4-dinitrophenyl hydrazine - H. Al-Saadawy, Nuha (University of Thi-Qar Journal of Science, 2016)
Ligand The development of 2,4-dinitrophenyl hydrazine with camphor under demonstrated conditions yielded another hydrazone ligand. The structures of metel (II) for example, copper, nickel, cobalt, zinc and iron with hydrazone have been composed from reacting between copper bromide, nickel chloride hexahydrate, cobalt chloride hexahydrate, zinc chloride, and iron bromide with hydrazone in 1:2 molar ratio. The ligand and their metal complexes have been detached in a solid state. The spectroscopic date of the structures proposes their 1:2 structures which are characterized by CHN, FT-IR and 1H NMR spectroscopy. From spectroscopic reviews I proposed the octahedral structure for the all structures and the outcomes are spoken to and talked about underneath.